Znanstveni doprinosi istraživanju zločina genocida počinjenog u Srebrenici jula 1995. godine / Scientific research Contribution Crimes of Genocide Committed in Srebrenica, July 1995. - Kuka, Ermin (Pregled: časopis za društvena pitanja / Periodical for social issues, 2016)
This text is a review of Zbornik radova Srebrenica 1995-2015: Evaluacija naslijeđa i dugoročnih posljedica genocida (Book of Proceedings: Srebrenica 1995-2015: Evaluation heritage and long-term consequences of genocide) from the international scientific conference held in Sarajevu, Tuzla and Srebrenica (Potočari) on 9-11 July 2015. (Institute for The Research of Crimes Against Humanity and International Law University of Sarajevo, Sarajevo, 2016, Book I and Book II).